2021
DOI: 10.1016/j.ejmech.2020.112905
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive intranasal administration route directly to the brain using dendrimer nanoplatforms: An opportunity to develop new CNS drugs

Abstract: There are several routes of administration to the brain, including intraparenchymal, intraventricular, and subarachnoid injections. The blood-brain barrier (BBB) impedes the permeation and access of most drugs to the central nervous system (CNS), and consequently, many neurological diseases remain undertreated. For past decades, to circumvent this effect, several nanocarriers have been developed to deliver drugs to the brain. Importantly, intranasal (IN) administration can allow direct delivery of drugs into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Studies regarding the binding of VivaGel ® to SARS-CoV-2 spike protein, thus blocking the interaction of the virus with the host human membrane ACE2 protein (the first event of infection), are ongoing, as are investigations into its use as an antiviral agent against COVID-19 via nasal or inhalational administration [ 97 ]. One of the important advantages of dendrimers is that they can reach the systemic circulation via multiple administration routes, such as oral, intravenous, transdermal, topical ocular [ 98 ] ( Figure 4 ) and nasal routes [ 99 ]. In an excellent review, Kuzmova and Minko highlighted the strong advantages of nanotechnology approaches for inhalation treatment of lung diseases [ 100 ].…”
Section: Dendrimers Used In Covid-19 Treatment: Few Clinical Examples But Limitless Possibilitiesmentioning
confidence: 99%
“…Studies regarding the binding of VivaGel ® to SARS-CoV-2 spike protein, thus blocking the interaction of the virus with the host human membrane ACE2 protein (the first event of infection), are ongoing, as are investigations into its use as an antiviral agent against COVID-19 via nasal or inhalational administration [ 97 ]. One of the important advantages of dendrimers is that they can reach the systemic circulation via multiple administration routes, such as oral, intravenous, transdermal, topical ocular [ 98 ] ( Figure 4 ) and nasal routes [ 99 ]. In an excellent review, Kuzmova and Minko highlighted the strong advantages of nanotechnology approaches for inhalation treatment of lung diseases [ 100 ].…”
Section: Dendrimers Used In Covid-19 Treatment: Few Clinical Examples But Limitless Possibilitiesmentioning
confidence: 99%
“…Co-delivery systems for drug delivery come in many designs. They may comprise carriers, where one or more drugs are packaged into liposomes, nanoparticles, hydrogels, dendrimers, or other vehicles [119,120], and some of these are being developed specifically for the purpose of intranasal delivery to reach the brain via the nose-to-brain route [121,122]. Studies with POH have also revealed characteristics that make this monoterpenoid suitable for the purpose of transporting other drugs directly to the brain via the nose-to-brain route.…”
Section: Intranasal Poh As a Co-delivery Systemmentioning
confidence: 99%
“…It is necessary for drugs to reach the brain for the treatment of schizophrenia. With respect to recent drug delivery technology into the brain, conjugations by BBB-penetrating peptides [ 152 , 153 ] and intranasal administration have been developed [ 154 , 155 ]. The combination of the synapse-protecting reagent and brain delivery methods could be used to treat schizophrenia.…”
Section: Potential Diagnosis/medication For Schizophrenia Based On Microglia–synapse Interactionmentioning
confidence: 99%